DNA Sensors’ Signaling in NK Cells During HHV-6A, HHV-6B and HHV-7 Infection - Bortolotti, Daria; Gentili, Valentina; Caselli, Elisabetta; Sicolo, Mariangela; Soffritti, Irene; D’Accolti, Maria; Barao, Isabel; Rotola, Antonella; Di Luca, Dario; Rizzo, Roberta (Frontiers in Microbiology, 2020)
Objectives: The host DNA sensor proteins TLR9, STING, IFI16 are central signaling molecules that control the innate immune response to cytosolic nucleic acids. Here we propose to investigate how Natural Killer (NK) cell infection by Human Herpesvirus (HHV)-6A, HHV-6B or HHV-7 is able to modify DNA sensor signaling in NK cells. Methods: We infected NK92 cell line and primary NK cells with cell-free inocula of HHV-6A, HHV-6B or HHV-7 and evaluated TLR9, STING, IFI16 pathway expression, by Real-Time PCR, Western Blot, immunofluorescence and flow cytometry, 1, 2, 3, 6 days post-infection. We evaluated NK cell cytokine-producing by Real-Time PCR and enzyme immunosorbent assay. Results: NK92 and primary NK cells were promptly infected by all viruses, as demonstrated by virus presence (DNA) and transcription (RNA) analysis. Our data show STING/STAT6 up-modulation in HHV-6A infected NK cells. NK cells infected with HHV-6B and HHV-7 up-regulated CCL3, CCL4, IFN-alpha, TNF-alpha, IL-8 and IFN-gamma and slightly induced IL-4, IL-8. HHV-6A infected NK cells up-regulated IL-4 and IL-13 and slightly induced CCL3, IL-10, IL-13, TNF-alpha, IL-8 and IFN-gamma. Conclusions: In conclusion, for the first time, we demonstrate, that HHV-6A, HHV-6B and HHV-7 infections are sensed differently by intracellular DNA sensors. HHV-6B and HHV-7 mainly lead to the active control of in vivo viral spreading by pro-inflammatory cytokine secretion via TLR9. HHV-6A infected NK cells conversely induced STING/STAT6 pathway, as a mechanism of anti-viral activation, but they were characterized by a Th2 type response and a non-cytotoxic profile, suggesting a potential novel mechanism of HHV-6A-mediated immunosuppression.